Satyric Chorus and its function in Aeschylean Satyric mÅ·thoi. Some notes on choral gestures and Silenus' actant role in Nethaulers - De Santis, Guillermo (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Centro de Estudios Helénicos, 2020)
The aim of this paper is to make visible some aspects of the dramatic role and the scenic function of the chorus in Aeschylean Satyric Drama, specifically in Fr. 47 to R, lines 821-832. The hypothesis of the paper argues that this choral song must be understood in dependence on the previous song of Silenus, lines 802-820, an estrophic pair with which it shows an obvious thematic relationship of complementarity. From the scenic point of view, the imbrication of the Chorus in the satyrical plot is direct and plays an actantial role that allows a scheme of integration and separation of Silenus in the choral action in an alternate movement as coryphaeus and actor. The interaction between both lyric passages would not only be noted in the mí½htos and in the language but also in the gestures of the Chorus, that contribute to organize the scene.